Gastropoda Community Structure in Mangrove Village Badarai, Malaka - Klau, Yosefina Hoar; Blasius Atini; Ludgardis Ledheng (Universitas Muhammadiyah Prof. Dr. Hamka, 2026)
Background: This study examined the structure of gastropod communities in the coastal mangrove ecosystem of Badarai Village, Malaka Regency. Methods: Sampling was conducted at two stations using the quadratic transect method with a total of 30 plots. Ecological analysis included the Shannon -Wiener Diversity Index (H'), Evenness Index (E), Simpson Dominance Index (C), and the relative abundance of each species. Results: The results of the study identified seven gastropod species, namely Terebralia semistriata, Telescopium telescopium, Terebralia palustris, Terebralia sulcata, Chicoreus capucinus, Nerita balteata, and Cerithidea quoyii. The species with the highest abundance was Terebralia semistriata, while Chicoreus capucinus and Nerita balteata showed the lowest abundance. The H' value at both stations was in the moderate category, with E also being moderate, indicating a relatively even distribution of individuals. Meanwhile, the C value was low, so no species truly dominated. Conclusions: Overall, these results indicate that the mangrove ecosystem of Badarai Village still supports the existence of gastropods with a fairly balanced community structure.